1989
DOI: 10.1021/j100362a022
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic mode selection due to the electrocapillary effect: the mercury beating heart in neutral and basic solutions

Abstract: The electrocapillary mechanism driving the oscillatory hydrodynamic modes of a "clean" (i.e., without organic contaminants) mercury drop in the absence of oxygen and in neutral and basic solutions was investigated. The electrocapillary driver can be mimicked by imposition of an external field oscillating with frequency vmax and amplitude AK about an appropriate voltage K0, where K0 is referenced to a standard potential. The hydrodynamic mode selection for a given K0 is controlled in a strictly reproducible and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…5 In our experiments with a single oscillator in a watch glass geometry, we find that potentials of the W tip with ∆ ca. -1000 mV favor concentric modes whereas low potentials with ∆ below -1300 mV select the deformation modes with 2-, 3-, and 4-fold symmetry axis.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…5 In our experiments with a single oscillator in a watch glass geometry, we find that potentials of the W tip with ∆ ca. -1000 mV favor concentric modes whereas low potentials with ∆ below -1300 mV select the deformation modes with 2-, 3-, and 4-fold symmetry axis.…”
Section: Resultsmentioning
confidence: 65%
“…4 In subsequent investigations, it was demonstrated that a number of different modes can be observed if one replaces the corroding iron nail by a tungsten tip and applies an adjustable voltage source instead of the fixed potential of the iron electrode. 5 These modes which comprise excitations with 2-, 3-, 4-, and 6-fold symmetry axes and also irregular motions have been termed hydrodynamic modes because they appear to be determined by the fluid mechanical properties of the mercury.…”
Section: Introductionmentioning
confidence: 99%
“…[108][109][110] In the other system,i nstead of the electrical connection,aHg droplet and oxidant crystal, for example, K 2 Cr 2 O 7 ,a re separately immersed into acidic solution with as mall spacing. One is the mercury droplets ystem in which am ercury dropleta nd Fe wire are placed in aH 2 SO 4 solution and connected through ap otentiometer.I nt he primary beatingm ercury heart system,g eometry of aH gd roplet peri-odically changes in time and is synchronized with the redox reaction between Hg and Fe.…”
Section: Self-propelleddropletsc Oupled With Chemical Reactionsmentioning
confidence: 99%
“…One is the mercury droplets ystem in which am ercury dropleta nd Fe wire are placed in aH 2 SO 4 solution and connected through ap otentiometer.I nt he primary beatingm ercury heart system,g eometry of aH gd roplet peri-odically changes in time and is synchronized with the redox reaction between Hg and Fe. [108][109][110] In the other system,i nstead of the electrical connection,aHg droplet and oxidant crystal, for example, K 2 Cr 2 O 7 ,a re separately immersed into acidic solution with as mall spacing. In this case, the Hg droplets hows spontaneous movement, the behavior of whichd epends on chemicalc omponent of the acid, that is, attractive to the crystal in H 2 SO 4 and an amoeba like crawling motion in HNO 3 .…”
Section: Self-propelleddropletsc Oupled With Chemical Reactionsmentioning
confidence: 99%
“…Inserting the measured dependence shown before that oscillations of the mercury beating heart can be driven by externally imposed electrical oscillations 18,19 . Analogously, we have driven the system externally (Fig.…”
Section: Evaluation Of the Measurementsmentioning
confidence: 91%